(:unas) unassigned - Charalambous, Andreas (My University, 2018)
2008- Scandinavian Journal of Caring Sciences 2010- BMC Medical Ethics 2009- International Journal of Nursing Studies 2012- Journal of Clinical Nursing 2007- European Journal of Oncology Nursing 2008- International Nursing Review 2011- Asian Nursing Research 2010- International Journal of Nursing Education Scholarship 2013- Journal of Pain and Symptom Control